PENGARUH VISUAL MERCHANDISING DAN BRAND PERSONALITY TERHADAP IMPULSE BUYING MELALUI POSITIVE EMOTION (STUDI PADA KONSUMEN MATAHARI DEPARTMENT STORE MALANG TOWN SQUARE) - Intan Mutiara Putri; N. Rachma; M. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT The purpose of this study is to determine the relationship between visual merchandising and brand personality on impulse buying which mediated by positive emotion. The data used is primary data by distributing questionnaires to consumers at Matahari Department Store Malang Town Square. The population taken in the study was 309 respondents and calculated using the Slovin formulaso that a sample of 76 respondents was obtained. Data analysis techniques in this study using validity tes, reliability test, normality test path analysis, t test and sobel test. Data obtained from questionnaire deployment is measured using a likert scale. Where the results of the analysis depend on the scores obtained from the respondents. The results of the study are (1) visual merchandising and brand personality directly influence impulse buying (2) visual merchandising and brand personality have a direct effect on positive emotion (3) positive emotion has a direct effect on impulse buying (4) visual merchandising and brand personality influence indirect to impulse buying through positive emotion as an intervening variable. Keywords : Visual merchandising, brand personality, impulse buying, positive emotion